2014
DOI: 10.1186/1865-1380-7-13
|View full text |Cite
|
Sign up to set email alerts
|

Patients in a private hospital in India leave the emergency department against medical advice for financial reasons

Abstract: BackgroundSome reports indicate financial concerns as a factor affecting ED patients leaving the acute care setting against medical advice (AMA). In India, no person is supposed to be denied urgent care because of inability to pay. Since a large proportion of the Indian health care system is financed by out-of-pocket expenses, we investigate the role of financial constraints for ED patients at a private hospital in India in leaving AMA.MethodsA prospective ED-based cross-sectional survey of patients leaving AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 8 publications
5
36
3
Order By: Relevance
“…Therefore, in this study, the distance and financial problems can be considered as the main causes of the DAMA. The results are consistent with the results of studies in Nigeria ( 21 , 28 ), India ( 25 ), and Tehran ( 27 ). The distance in addition to the cost for patients can increase their willingness for DAMA.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, in this study, the distance and financial problems can be considered as the main causes of the DAMA. The results are consistent with the results of studies in Nigeria ( 21 , 28 ), India ( 25 ), and Tehran ( 27 ). The distance in addition to the cost for patients can increase their willingness for DAMA.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have been conducted to investigate the causes of DAMA. Dissatisfaction with the care received, an enhanced sense of well-being ( 16 ), financial problems ( 21 , 25 27 ), lack of access to skilled and qualified physicians, lack of advanced medical services due to lack of essential medical equipment, high burden of patients referral, and bustle in medical centers ( 11 ), dissatisfaction with the medical staff, dissatisfaction with the hospital environment, not achieving a satisfactory result from treatment ( 28 ), and prolonging the stay of patients ( 29 ) are of investigated reasons in the studies. In addition to the reasons stated, several variables have been examined in studies and have been confirmed as predictors of DAMA.…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare in Delhi is provided by a mix of for-profit hospitals, and relatively low-cost public hospitals 43. Patients often leave for-profit hospitals against medical advice for financial reasons 44 45. It is standard medico-legal practice across India to treat all injuries as potentially criminal cases that are registered as medico-legal cases and reported to the police.…”
Section: Methodsmentioning
confidence: 99%
“…[ 1 ] Despite the widespread nature of this problem, there has been little data evaluating incidence, reasons, and outcome of patients leaving DAMA. Studies have focused on specific patient groups such as patients admitted to the emergency department[ 7 ] or psychiatric/orthopedic patients. [ 8 ] We did not find any studies specifically evaluating this in critically ill patients in India.…”
Section: Discussionmentioning
confidence: 99%